To the ends of Japan : premodern frontiers, boundaries, and interactions - Batten, Bruce Loyd (University of Hawaiʻi Press, 2003)
"To the Ends of Japan tackles the "big questions" on Japan by focusing on its borders, broadly defined to include historical frontiers and boundaries within the islands themselves as well as the obvious coastlines and oceans. Batten provides compelling arguments for viewing borders not as geographic "givens," but as social constructs whose location and significance can, and do, change over time. By giving separate treatment to the historical development of political, cultural, and ethnic borders in the archipelago, he highlights the complex, multifaceted nature of Japanese society, without losing sight of the more fundamental differences that have separated Japan from its nearest neighbors in the archipelago and on the Eurasian continent." "Unusually wide ranging in scope and highly eclectic in approach, To the Ends of Japan offers a fresh and coherent view of Japanese history that will appeal to both students of Japan and East Asia and readers with a general interest in frontiers and borders."--Jacket